Cutting age effects on yield and nutritive values of Napier Pakchong (Cenchrus purpureus cv. Pakchong) - Haryani H. (2024)
Napier Pakchong (Cenchrus purpureus cv. Pakchong) is another cultivar of Napier grass which was introduced from Thailand. This cultivar is mostly adapted for local soil conditions in Malaysia, has high yield and relatively high protein content making Napier Pakchong suitable for ruminant feeding. This experiment was carried out to determine the dry matter yield and nutritive values of Napier Pakchong at three different cutting ages (6ᵗʰ, 7ᵗʰ and 8ᵗʰ weeks old). All plots underwent a standard preparation and basal fertilizers during grass establishment. The cutting treatments were carried out 3 times at the 6ᵗʰ, 7ᵗʰ and 8ᵗʰ weeks. After each harvest, the rates of maintenance fertilizer used were NPK 150:60:100 (kg/ha/year). The harvested forage was weighed and sent for dry matter yield and proximate analysis. The data were analysed by one way analysis of variance (ANOVA) using the programme of SAS (Package Version 9.4). The difference between treatment means was measured by Duncan’s Multiple Range Test (DMRT) at 5 % level of significance. The data showed that dry matter yield production increased in line with the cutting interval. Crude protein (CP) value declined as the harvesting interval increased. Even though the CP value declined, the CP percentage still fulfils the protein requirements for ruminants. It is suggested that Napier Pakchong harvested at 7th to 8th weeks due to optimum dry matter yield and nutritive value.